2022
DOI: 10.1002/ajb2.1864
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and development of inflorescences and floral symmetry in Solanaceae

Abstract: The inflorescences of Solanaceae are unique and complex, which has led to long-standing disputes over floral symmetry mainly due to different interpretations of the cyme-like inflorescence structure. The main disagreements have been over how the phyllomes associated with the flower were arranged relative to the inflorescence axis especially during early flower initiation. Methods: Here we investigated the evolution of inflorescences in Solanaceae by analyzing inflorescence structure in the context of phylogeny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…A recent study on the evolution and development of inflorescences in Solanaceae, the sister family of Convolvulaceae in Solanales (e.g., [76,77], showed that both scorpioid and dichasial cymes are present in the family, and the latter are likely derived from the former [78]. Within Convolvulaceae, no comparative or character evolution inflorescence study has been conducted either at the level of the entire family or in different genera.…”
Section: Inflorescence Architecture In Solanaceae and Convolvulaceaementioning
confidence: 99%
“…A recent study on the evolution and development of inflorescences in Solanaceae, the sister family of Convolvulaceae in Solanales (e.g., [76,77], showed that both scorpioid and dichasial cymes are present in the family, and the latter are likely derived from the former [78]. Within Convolvulaceae, no comparative or character evolution inflorescence study has been conducted either at the level of the entire family or in different genera.…”
Section: Inflorescence Architecture In Solanaceae and Convolvulaceaementioning
confidence: 99%
“…Angiosperm flowers can be divided into the following three types according to the presence or absence of a plane of symmetry: (1) radially symmetrical flowers (actinomorphic) with multiple planes of symmetry, (2) bilaterally symmetrical flowers (zygomorphic) with only one plane of symmetry, and (3) asymmetrical flowers with no plane of symmetry [ 39 , 40 , 41 , 42 ]. Studies of fossils have revealed that angiosperm flowers were originally actinomorphic and that zygomorphic flowers arose during evolution [ 43 , 44 , 45 , 46 ]. Wild-type snapdragon, which has typical zygomorphic flowers, is a model plant for studying floral symmetry [ 47 ].…”
Section: Introductionmentioning
confidence: 99%